2019
DOI: 10.1371/journal.pone.0226562
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and poor sleep quality among Han and Manchu ethnicities in a large, rural, Chinese population

Abstract: ObjectivesTo estimate the relationship between sleep quality and depression, among Han and Manchu ethnicities, in a rural Chinese population.MethodsA sample of 8,888 adults was selected using a multistage cluster and random sampling method. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Depressive symptoms were assessed via the Center for Epidemiological Survey, Depression Scale (CES-D). Logistic regression was conducted to assess associations between sleep quality and depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
6
7
2
1
Order By: Relevance
“…The finding of the current study also revealed that, PSQI score has strongly associated with anxiety symptoms and moderately correlated to depression and perceived stress in positive direction. This was in agreement with many previous studies [15,[44][45][46][47]. This probably due to the fact that anxiety, depression and stress have the capacity to disturb individual's quality of life and leads to sleep disturbances [48] specifically during pandemic crisis [13].…”
Section: Discussionsupporting
confidence: 92%
“…The finding of the current study also revealed that, PSQI score has strongly associated with anxiety symptoms and moderately correlated to depression and perceived stress in positive direction. This was in agreement with many previous studies [15,[44][45][46][47]. This probably due to the fact that anxiety, depression and stress have the capacity to disturb individual's quality of life and leads to sleep disturbances [48] specifically during pandemic crisis [13].…”
Section: Discussionsupporting
confidence: 92%
“…Facebook users with poor sleep quality tend to experience depression. This conclusion has been found in previous studies of Supartini et al (2016), O'Leary et al (2017, Li et al (2018), Liu et al (2019), and Richardson et al (2019). In this study, the relationship between poor sleep quality and depression may be related to stress.…”
Section: Discussionsupporting
confidence: 88%
“…For depression, Baglioni et al (2011) indicated that people with insomnia are twice as likely to develop depression as those who do not have trouble sleeping. In addition, poor sleep quality contributes to the development of depression (Supartini et al, 2016;O'Leary et al, 2017;Li et al, 2018;Liu et al, 2019;Richardson et al, 2019). According to Zhang et al (2018), individuals with poor sleep quality are at risk of experiencing depression due to the development of stress symptoms.…”
Section: Sleep Quality and Mental Health Outcomesmentioning
confidence: 99%
“…No DSC3, os idosos relatam a má qualidade do sono relacionada ao estado de solidão. Sobre esses achados, estudos anteriores realizados com população chinesa e holandesa, que associaram a relação entre qualidade do sono e depressão, evidenciaram que os resultados indicaram que fatores demográficos, familiares, de estilo de vida e sociais afetavam distúrbios do sono, e ainda revelaram a prevalência de má qualidade do sono associados com problemas de saúde mental, incluindo a depressão (23,24) .…”
Section: Ic3: Isolamento Social Como Desencadeador Da Depressãounclassified